2022
DOI: 10.24256/foster-jelt.v3i2.89
|View full text |Cite
|
Sign up to set email alerts
|

The Error Analysis of Google Translate and Bing Translator in Translating Indonesian Folklore

Abstract:           The objective of this research is to find out the lexical errors made by Google Translate and Bing Translator in translating Indonesian folklore "Princess Tandampalik" and "Sigarlaki and Limbat." The research applied the qualitative method. The data were analyzed using hybrid taxonomy of error analysis from Vilar, et al. The results of this research show that Google Translate made 103 errors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…Fourth, Yudiarti (2019) states that the use of Microsoft Translator is still not feasible to be used to translate texts without involving translation experts by using suitable proofreading and editing. Fifth, Thayyib (2022) states that the incorrect term is the most common error identified in translations produced by Google Translate and Bing Translator with 152 errors. The majority of the wrong terms came in the translation of adjectives and adverbs, which Google Translate and Bing Translator rendered as nouns.…”
Section: Several Previous Studies Have Been Conducted Related To Onli...mentioning
confidence: 99%
“…Fourth, Yudiarti (2019) states that the use of Microsoft Translator is still not feasible to be used to translate texts without involving translation experts by using suitable proofreading and editing. Fifth, Thayyib (2022) states that the incorrect term is the most common error identified in translations produced by Google Translate and Bing Translator with 152 errors. The majority of the wrong terms came in the translation of adjectives and adverbs, which Google Translate and Bing Translator rendered as nouns.…”
Section: Several Previous Studies Have Been Conducted Related To Onli...mentioning
confidence: 99%
“…In the contemporary era of globalization, machine translation has emerged as a crucial facilitator for cross-language communication (Araújo et al, 2020). Prominent machine translation programs, such as Google Translate and Bing Microsoft Translator, have witnessed a notable surge in popularity in recent times (Jufriadi et al, 2022). This translation technology empowers users to promptly and precisely convert text from one language to another (ElShiekh, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, several studies have been conducted to examine translation errors in machine translation. Among them have analyzed common types of translation errors (Abu-Ayyash, 2017; Almahasees & Mahmoud, 2022;Jufriadi et al, 2022), In the study, a qualitative approach was employed to identify common errors in machine translation. The qualitative approach utilized in the research aimed to delve into and comprehend the detailed aspects of these errors, thereby providing a more profound insight into the performance of machine translation.…”
Section: Introductionmentioning
confidence: 99%
“…It was discovered, based on the study's findings and discussion, that Google Translate produced reasonably accurate translations of Indonesian text into English. The second research was conducted by (Jufriadi et al, 2022) entitled The Error Analysis of Google Translate and Bing Translator in Translating Indonesian Folklore. The research found that the most common type of error made by Google Translate and Bing Translator in translating Indonesian folklore "Putri Tandampalik" and "Sigarlaki dan Limbat" into English is the incorrect word.…”
Section: Introductionmentioning
confidence: 99%